EFEKTIVITAS PENGGUNAAN GOOGLE CLASSROOM SEBAGAI PLATFORM PEMBELAJARAN DARING PADA MASA WABAH COVID-19 MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Rohani, Rohani; Suarman, Suarman; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effectiveness of using Google Classroom as an online learning platform during the Covid-19 outbreak for economic education students, FKIP University of Riau. This research was conducted at the Economic Education Study Program, FKIP, Riau University. This research uses quantitative method. The population of this research is the economic education students of FKIP Riau University class of 2018 and class of 2019 with a total of 152 students. Samples were taken by Proportional Random Sampling. Data collection techniques were carried out by distributing questionnaires or questionnaires using Google from viamessages WhatsApp for the 2018 and 2019 economic education student groups. The results showed that the effectiveness of usingeffective. Google Classroom as an online learning platform during the COVID-19 outbreak, economic education students of FKIP University of Riau was veryeffective with an average value of 63.33%.Key Words: Effectiveness , Google Classroom, Online Learning, Covid-19 Outbreak